Extraction of novel antioxidants from seaweed: A review - Evangeline Yvonne Stidi; Nazirah Mingu; Mohd Hafiz Abd Majid; Juferi Idris; Mohd Sani Sarjadi (Faculty of Science and Natural Resources, 2021)
The aim of this review is to know the different oxidation extraction methods from seaweeds including solid-liquid extraction, pressurized liquid extraction, supercritical fluid extraction and other green extraction techniques. Those extraction efficiency and composition are affected by the parameters applied during extraction process such as solvent added, solid-liquid ratio, extraction time and heating rate. It is obligatory to know the most suitable method of seaweed extraction that can derive high yields of its bioactive compounds.